Antibacterial activity of alkyl gallates against Xanthomonas citri subsp. citri - Silva, I. C. [UNESP]; Regasini, L. O. [UNESP]; Petrãnio, M. S. [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Belasque, Jr.; Sacramento, L. V S [UNESP]; Ferreira, H. [UNESP] (American Society for Microbiology, 2013)
The plant-pathogenic bacterium Xanthomonas citri subsp. citri is the causal agent of Asiatic citrus canker, a seriousdisease that affects all the cultivars of citrus in subtropical citrus-producing areas worldwide. There is no curative treatment for citrus canker; thus, the eradication of infected plants constitutes the only effective control of the spread ofX. citri subsp. citri. Since the eradication program in the state of São Paulo, Brazil, is under threat, there is a clear risk of X. citri subsp. citri becoming endemic in the main orange-producing area in the world. Here we evaluated the potential use of alkyl gallates to prevent X. citri subsp. citri growth. These esters displayed a potent anti-X. citri subsp. citri activity similar to that of kanamycin (positive control), as evaluated by the resazurin microtiter assay (REMA). Thetreatment of X. citri subsp. citri cells with these compounds induced altered cell morphology, and investigations of the possible intracellular targets using X. citri subsp. citri strains labeled for the septum and centromere pointed to a commontarget involved in chromosome segregation and cell division. Finally, the artificial inoculation of citrus with X. citri subsp. citri cells pretreated with alkyl gallates showed that the bacterium loses the ability to colonize its host, which indicates the potential of these esters to protect citrus plants against X. citri subsp. citri infection. © 2013, American Society for Microbiology.
Keywords: antiinfective agent; gallic acid alkyl ester; gallic acid derivative; kanamycin; unclassified drug; antibacterial activity; bacterial cell; bacterial colonization; bacterial growth; cell division; cell structure; centromere; chromosome segregation; controlled study; drug potency; drug targeting; growth inhibition; inoculation; nonhuman; priority journal; Xanthomonas citri; Anti-Bacterial Agents; Citrus; Gallic Acid; Molecular Structure; Plant Diseases; Plant Leaves; Xanthomonas; Bacteria (microorganisms)